Expansion of the phenotypic and molecular spectrum of CWF19L1‐related disorder. Issue 5 (11th January 2023) - Alvarez, Carolina; Grimmel, Mona; Ebrahimi‐Fakhari, Darius; Paul, Victoria G.; Deininger, Natalie; Riess, Angelika; Haack, Tobias; Gardella, Elena; Møller, Rikke S.; Bayat, Allan
Abstract: Pathogenic variants in CWF19L1 lead to a rare autosomal recessive form of hereditary ataxia with only seven cases reported to date. Here, we describe four additional unrelated patients with biallelic variants in CWF19L1 (age range: 6–22 years) and provide a comprehensive review of the literature. The clinical spectrum was broad, including mild to profound global developmental delay; global or motor regression in infancy or adolescence; childhood‐onset ataxia and cerebellar atrophy; and early‐onset epilepsy. Since only two previously reported patients were adults, our cohort expands our understanding of the evolution of symptoms from childhood into early adulthood. Taken together, we describe that CWF19L1‐related disorder presents with developmental and epileptic encephalopathy with treatment‐resistant seizures and intellectual disability in childhood followed by progressive ataxia and other extrapyramidal movement disorders in adolescence. Abstract : The complex clinical spectrum of CWF19L1‐related illness includes both neurodevelopmental and degenerative features. Symptoms include global developmental delay followed by regression in infancy or adolescence, childhood‐onset epilepsy, ataxia and cerebellar atrophy.